Effect of maize residue on five maize hybrids - Wahab, Zakaria; Kaspar, Thomas C. (Malaysian Society of Applied Biology, 1990)
Maize yield declines as the number of consecutive years of maize in a rotation increases. This decrease in yield may be explained by allelochemicals released from residues of the previous crop. Maize residues of Pioneer X4472 collected after harvest were tested for an allelopathic effect on five maize hybrids in greenhouse pots. Results from this study showed that shredded residue mixed with soil had both a physical and a chemical effect on maize seedlings growth. Ground residue mixed with the soil usually inhibited maize growth. Incorporating the residues into the soil caused a greater inhibitory effect on plant growth than surface residue. Residue on the surface, however, usually increased shoot growth of maize plants. Maize hybrids also showed some indications of differences in their responses to maize residue.